Intrinsic polyphenol oxidase-like activity of gold@platinum nanoparticles. Issue 78 (26th August 2015) - Lee, Jo-Won; Yoon, Sohee; Lo, Y. Martin; Wu, Haohao; Lee, Sook-Young; Moon, BoKyung
<x xml:space="preserve">Abstract</x> Au@Pt NPs showed PPO mimetic activity over a wider range of pH and temperatures compared to PPO. In the oxidation of all substrates, Au@Pt NPs exhibited higher affinity to the substrates, especially to catechol and pyrogallol, compared with PPO.